(3ef hUGjG GdEeGe GdTGaYis - (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY ,J (B204 (3g` s
(3ChdgG (B:s
(3Ef QeJ jG gPG VjGY GdeGd aYGed GdLdGH ddQajb hYGed GdadGM jG UOjbi hYGed GdeadS hGdeQGcHi aGMPQgeG hdG Jbd PG UGMHi s
(3BNQgG (B:s
(3hYGed GdeOjhf ddSdWGf jJHbi gjf GdNjQ hGMQU Ydi GdeGd ef GdJHPjQ JYjT Hjf GdfGS cGdCejQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs